Reduced optimism and a heightened neural response to everyday worries are specific to generalized anxiety disorder, and not seen in social anxiety. Issue 10 (14th March 2017) - Blair, K. S.; Otero, M.; Teng, C.; Geraci, M.; Ernst, M.; Blair, R. J. R.; Pine, D. S.; Grillon, C.
Abstract : Background: Generalized anxiety disorder (GAD) and social anxiety disorder (SAD) are co-morbid and associated with similar neural disruptions during emotion regulation. In contrast, the lack of optimism examined here may be specific to GAD and could prove an important biomarker for that disorder. Method: Unmedicated individuals with GAD ( n = 18) and age-, intelligence quotient- and gender-matched SAD ( n = 18) and healthy ( n = 18) comparison individuals were scanned while contemplating likelihoods of high- and low-impact negative (e.g. heart attack; heartburn) or positive (e.g. winning lottery; hug) events occurring to themselves in the future. Results: As expected, healthy subjects showed significant optimistic bias (OB); they considered themselves significantly less likely to experience future negative but significantly more likely to experience future positive events relative to others ( p < 0.001). This was also seen in SAD, albeit at trend level for positive events ( p < 0.001 and p < 0.10, respectively). However, GAD patients showed no OB for positive events ( t 17 = 0.82, n.s .) and showed significantly reduced neural modulation relative to the two other groups of regions including the medial prefrontal cortex (mPFC) and caudate to these events ( p < 0.001 for all). The GAD group further differed from the other groups by showing increased neural responses to low-impact events in regions including the rostral mPFC ( p < 0.05 for both). Conclusions: The neural dysfunction identified here may represent a unique feature associated with reduced optimism and increased worry about everyday events in GAD. Consistent with this possibility, patients with SAD did not show such dysfunction. Future studies should consider if this dysfunction represents a biomarker for GAD.